Análise da influência da suplementação de cafeína sobre indicadores hemodinâmicos no powerlifting paralímpico - Menezes, Jainara Lima (2022)
Abstract: Exercise, including resistance exercise with high loads, has positive hemodynamic responses, such as a reduction in systolic (SBP), diastolic (DBP) blood pressure, heart rate (HR), double product (DP) and volume of myocardial oxygen (MVO2). supplements like caffeine (CA), used to improve performance, tends to interfere with BP and HR. Objective: To analyze the effects of AC supplementation on hemodynamic indicators in Paralympic powerlifting (PP). Methods: 14 male PP athletes participated (32.4 ± 8.5 years; 81.7 ± 21.9 kg). Two conditions were evaluated: supplementation with CA Anhydrous 9mg/kg and placebo (PL). The adapted bench press was used, with 5x5 at 80% 1RM. We evaluated BP, HR, DP and MVO2, before, after, 5, 10, 20, 30, 40, 50, 60 minutes and 24 hours later. Results: The AC presented higher absolute values in the pressure indicators than the PL, 24 hours there was an inversion. The HR was higher in the AC, after 10min it showed a reduction. The DP and MVO2 in the CA showed higher absolute values than the PL, 24 hours later there was an inversion. Conclusion: AC had a hypotensive effect after 24 hours and did not present risks related to DP and MVO2, demonstrating the safe use of this supplement in adapted strength sports.